Applying geospatial technology to identify soil erosion risks in the context of climate change in Yen Chau district, Son La province - Van Truong, Vu; Tri Son, Ha; Thi Bich Hao, Nguyen; Hai Hoa, Nguyen; Van Dung, Phan; Thi Thuy Anh, Nguyen (Journal of Forestry Science and Technology, 2023)
This article presents the results of applying geospatial technology to assess soil erosion for Yen Chau district. Geospatial Technology was applied to build maps of factors affecting soil erosion such as: rain erosion coefficient map (R), soil erosion resistance coefficient map (K), terrain erosion coefficient map (LS), cover erosion coefficient map (C) and farming practices (P). Improved universal soil loss equation (RUSLE) due to Wischmeier and Smith was used to create soil erosion maps. The research results have determined the level of erosion and the proportion of eroded area corresponding to each level in Yen Chau district, Son La province. Research results showed that the majority of the area (59.79%) falls into the Slight or Moderate severity category, a significant portion of the area (39.53%) falls into the High and Very high severity categories, a small percentage of the area (0.69%) falls into the Severe category. In addition, the research team built two soil erosion maps for the study area under two climate change scenarios RCP4.5 and RCP8.5 (in terms of rainfall) for the period 2046-2065. According to the result, the data for slight, moderate, and high soil erosion levels all decrease in both scenarios. While, the data for high and very high soil erosion levels increase significantly in both scenarios. This suggests that the situation of soil erosion may become more severe in the future according to both climate scenarios RCP4.5 and RCP8.5.